God knows there's need Christian responses to poverty - Holman, Susan R. (New York ; Oxford : Oxford University Press, 2009)
In this volume, Susan Holman looks at how the Christian tradition, ancient and modern, has contemplated the subject of poverty and encourages the reader to reflect on the social issues of injustice and need. She alternates images from late antiquity and the patristic period with stories from contemporary American life.
Description based on print version record.
Keywords: Poverty -- Religious aspects -- Christianity -- History of doctrines; Armoede; Religieuze aspecten; Electronic books